A Role for the Amygdala in Impairments of Affective Behaviors Following Mild Traumatic Brain Injury - McCorkle, Taylor A.; Barson, Jessica R.; Raghupathi, Ramesh (Frontiers in Behavioral Neuroscience, 2021)
Mild traumatic brain injury (TBI) results in chronic affective disorders such as depression, anxiety, and fear that persist up to years following injury and significantly impair the quality of life for patients. Although a great deal of research has contributed to defining symptoms of mild TBI, there are no adequate drug therapies for brain-injured individuals. Preclinical studies have modeled these deficits in affective behaviors post-injury to understand the underlying mechanisms with a view to developing appropriate treatment strategies. These studies have also unveiled sex differences that contribute to the varying phenotypes associated with each disorder. Although clinical and preclinical studies have viewed these disorders as separate entities with unique neurobiological mechanisms, mechanistic similarities suggest that a novel approach is needed to advance research on drug therapy. This review will discuss the circuitry involved in the expression of deficits of mild TBI in human and animal studies and provide evidence that the manifestation of impairment in affective behaviors stems from an amygdala-dependent emotional processing deficit. It will highlight mechanistic similarities between deficits that can potentially advance mild TBI drug therapy by investigating treatment for the various deficits in affective behaviors as one entity, potentially requiring the same treatment.